Plasma metabolomics pilot study suggests age and sex-based differences in the metabolic response to traumatic injury. Issue 12 (December 2018) - Lusczek, Elizabeth R.; Myers, Cole; Popovsky, Kimberly; Mulier, Kristine; Beilman, Greg; Sawyer, Robert
Abstract: Introduction: Age and sex affect outcomes from trauma. Older patients tend to be under-triaged, consume more healthcare resources, and experience worse outcomes relative to younger patients. Sex has also been associated with different outcomes, with women experiencing better outcomes than men. While baseline metabolism differs with both age and sex, no study has examined how these differences affect the response to trauma. We used high-throughput metabolomics to assess metabolic differences associated with blunt trauma according to age and sex. Methods: Metabolic profiles were constructed using nuclear magnetic resonance spectroscopy for trauma patients age 21–40 years (n = 20, 55% male) and >65 years (n = 22, 41% male) from plasma samples obtained on Day 1 and Day 3 of each patient's hospital stay. These were compared to profiles constructed from plasma obtained from healthy controls of the same age (21–40: n = 23, 61% male; 65+: n = 26, 50% male). Differences in metabolic profiles were assessed with partial least squares discriminant analysis. Results: Trauma elicits an overwhelming global stress response that includes more subtle differences in metabolism related to age and gender. Significant differences due to normal aging were also identified. Many of the metabolites measured were present in similar levels in healthy controls age 65+ as they were in trauma patients of all ages. Sex-based differences in metabolism were observed in younger trauma patients on Day 3 but not in older patients. Conclusions: Differences in energy metabolism and oxidative stress were implicated in the response to trauma in all patients. Older trauma patients may enter the trauma state with pre-existing oxidative stress and energy deficits that complicate recovery. Sex-based differences in recovery from trauma support the large body of work demonstrating the role of sex in recovery from trauma.